(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to clarify the advantages of statistical sampling method and provided the scientific basis of the auditor was able to defend the future of any objection to the validity of his opinion on the financial statements of the restrictions of personal rule as much as possible during the stages of the general Company for Cotton industries.Aresearc An applied study in the Board of supreme Audit (the accounts of the cotton industry), have been used, a researcher at the theoretical side to achieve the objectives of the research methodology descriptive inference in the collection and analysis of financial statements of the circle (sample) for the financial year (2008). To achieve the objectives of the field study was designed questionnaire commensurate with the variables of the research problem and hypotheses. Questionnaire was distributed to the auditors of financial statements in the Audit Court, which reached number (100) questionnaire, the responses were (82) questionnaire are analyzed, representing a ratio of (82%). The most important results of the search importance of the use of professional judgment (Profile) to the auditor, including risk of bias and the inability to measure the risk of audit and was the method of selecting a plan preview that fit with the goal of choice, and select each of the size of the community in question and the sample size is appropriate, selection of of sample in a manner ensure the safety of their representation of the community it was drawn, that the application of the style of statistical sampling in an environment audit requires the auditor to be aware of the mechanisms for implementation of this method is sufficient to plan the audit process, taking into account the lack of bias in order to give each individual the same chance to be among the sample, as well as need to take into account the objectives of sampling and the characteristics of the society that will be taken from the sample and the nature of evidence required.